Notes on the Ancient Relics preserved at Dunvegan Castle, and the Heraldry of the Family of MacLeod (Proceedings of the Society of Antiquaries of Scotland, 1912)
[The journal notes that this paper has been postponed to the next volume of the Proceedings on account of the illustrations.]